Characterizing the Relationship Between the COVID-19 Pandemic and U.S. Classical Musicians' Wellbeing - Wang, Grace; Fram, Noah R.; Carstensen, Laura L.; Berger, Jonathan (Frontiers in Sociology, 2022)
The COVID-19 pandemic has devastated the economic and social wellbeing of communities worldwide. Within the general population, certain groups are at greater risk than others, namely, persons with pre-existing mental disorders and those disproportionately impacted by the economic strain of the pandemic (Diaz et al. 2021; Calderón-Larrañaga et al. 2020) . Classical musicians, who bear a disproportionately high incidence of mental illnesses, and whose subsistence is primarily reliant upon live performances (van Fenema and van Geel 2014), fall into both categories. The COVID-19 pandemic has greatly harmed the classical music industry, silencing the world’s concert halls and theatres. In an industry characterized by instability, a shock as great as COVID-19 may bring negative effects that far outlast the pandemic itself. This study investigates the wellbeing of classical musicians during the COVID-19 pandemic. 68 professional classical musicians completed a questionnaire composed of validated measures of future time horizons, emotional experience, social relationships, and life satisfaction. Findings show that feelings of loneliness had a significant negative association with other measures of wellbeing and were significantly mediated by increased social integration and perceived social support from colleagues, friends, and family. These findings help to characterize the present psychological, emotional, and social wellness of classical musicians in the United States, the first step towards mitigating the hazardous impacts of COVID-19 on this vulnerable group’s mental health and wellness.